2003
DOI: 10.1021/jf034350r
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Black Drum and Sheepshead Seabream Skin Collagen

Abstract: Acid-soluble collagen (ASC) and pepsin solubilized collagen (PSC) were isolated from the skins of black drum (Pogonias cromis) and sheepshead seabream (Archosargus probatocephalus) harvested in the Gulf of Mexico coastal waters. The yields of ASCs on dry basis from black drum and sheepshead were estimated at 2.3 and 2.6%, and the yields of PSCs were 15.8 and 29.3%, respectively. Analyses of molecular weight profile, amino acid composition, and secondary structure showed that the skin collagens from both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
84
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 17 publications
18
84
1
3
Order By: Relevance
“…This characterisation is also consistent with the findings of Nomura et al (1996), who adopted the same method. In the present study, three distinct bands of molecular weights ranging from 112 to 220 kDa in C. catla and from 114 to 210 kDa in C. mrigala were observed; these findings were similar to those reported by Ogawa et al (2003) and Yung et al (2005). The isolated collagen may be type I, which was previously observed by Kimura et al (1993) and Muyonga et al (2004), who reported that the carp skin, scale, and bone collagen was the type I based on its electrophoretic mobility.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This characterisation is also consistent with the findings of Nomura et al (1996), who adopted the same method. In the present study, three distinct bands of molecular weights ranging from 112 to 220 kDa in C. catla and from 114 to 210 kDa in C. mrigala were observed; these findings were similar to those reported by Ogawa et al (2003) and Yung et al (2005). The isolated collagen may be type I, which was previously observed by Kimura et al (1993) and Muyonga et al (2004), who reported that the carp skin, scale, and bone collagen was the type I based on its electrophoretic mobility.…”
Section: Resultssupporting
confidence: 93%
“…1). These results are consistent with the findings of Ogawa et al (2003) and Zhang et al (2007), who also reported lack of a significant difference between the subunit molecular masses of the collagen from fins and scales. The C. catla fin collagen was run in wells 9 and 10 and revealed six fractions in each well with molecular weights of 70, 82, 111, 120, 180 and 201 kDa (Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…But, the outbreak of highly infectious and contagious diseases such as bovine spongiform encephalopathy (BSE), transmissible spongiform encephalopathy (TSE) and food and mouth disease (FMD) in pigs and cattle has limited the use of collagen derived from them. Therefore, many scientists have been focusing to find out alternative sources for collagen and they found different organisms from marine source such as black drum (Pogonia cromis) (Ogawa et al 2003), brownstripe red snapper (Lutjanus vitta) (Jongjareonrak et al 2005), ocellate puffer fish (Takifugu rubripes) (Nagai et al 2002) and leather jacket (Odonus niger) (Muralidharan et al 2011). However, collagen from freshwater fish, were rarely reported, except for the Nile perch (Lates niloticus) (Muyonga et al 2004), grass carp (Ctenopharyngodon idella) (Zhang et al 2007) and channel catfish (Ictalurus punctaus) ).…”
Section: Introductionmentioning
confidence: 99%